VEGETATION AS A TOOL FOR THERMAL REGULATION OF URBAN MICROCLIMATE IN ARID REGIONS - Badache, H; Alkama, Dj (university of el oued/جامعة الوادي, 2021)
The city of Biskra is known by its hot and arid climate; its outdoor spaces know extremely high temperatures during t he s ummer period, which affect thermal comfort, well being, user’s satisfaction in public spaces, such as the "Revolution’s plaza" which known by considerable attendance and a particular design. This study, focuses on the role of the urban vegetation on th e th ermal regulation in the open space. The main purpose is to study the effect of vegetation on the urban microclimate of this space “Revolution plaza”, through a site investigation, in order to measure the local climate and compare the results with weath er’s station data. After that, an improvement case is suggested by simulation by Envi Met 4 software. The results show the significant effect of the trees and natural surfaces in decreasing the heat transfer and temperatures degrees; which provides a favor able microclimate in this open space
Article
Keywords: Vegetation A rid climate P ublic space S imulation h ot region; Biskra.